Trajectory-Aware Mobile Search - Krumm, John; Teevan, Jaime; Karlson, Amy; Brush, A.J. (CHI 2012, 2012)
Most location-aware mobile applications only make use of the user’s current location, but there is an opportunity for them to infer the user’s future locations. We present Trajectory-Aware Search (TAS), a mobile local search application that predicts the user’s destination in real-time based on location data from the current trip and shows search results near the predicted location. TAS demonstrates the feasibility of destination prediction in an interactive mobile application. Our user study of TAS shows using predicted destinations to help select search results positively augments the local search experience.